2016
DOI: 10.1039/c6ra01891b
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine monophosphate-capped gold(i) nanoclusters: synthesis and lanthanide ion-induced enhancement of their luminescence

Abstract: Reduction of Au3+ in the presence of just AMP and HEPES, combined with light exposure, gives rise to luminescent, water-soluble Au+ nanoclusters. Their photoluminescence is considerably enhanced by adding Y3+ or Yb3+, which leads to Au+/Y3+ and Au+/Yb3+ NCs, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…Although the cations might reduce the Debye length of the electrostatically charged nanoparticles, the self‐assembly cannot be explained based on solely screening effects in the applied ionic strength range as the control experiments show (applying NaCl instead of YCl 3 or YbCl 3 ). These findings are in good agreement with the revealed effect of the lanthanides on the surface of gold nanoparticles modified by MPA and MUA [ 44,47 ] and emphasize the importance of the ligand replacements process in the framework of our self‐assembly experiments.…”
Section: Resultssupporting
confidence: 89%
“…Although the cations might reduce the Debye length of the electrostatically charged nanoparticles, the self‐assembly cannot be explained based on solely screening effects in the applied ionic strength range as the control experiments show (applying NaCl instead of YCl 3 or YbCl 3 ). These findings are in good agreement with the revealed effect of the lanthanides on the surface of gold nanoparticles modified by MPA and MUA [ 44,47 ] and emphasize the importance of the ligand replacements process in the framework of our self‐assembly experiments.…”
Section: Resultssupporting
confidence: 89%
“…The reaction of AuNC naked with AMP failed to lead to luminescent NCs. We have previously reported the preparation of luminescent AuNC@AMP/HEPES (hydroxyethyl piperazineethanesulfonic acid) by reaction of HAuCl 4 with HEPES in the presence of AMP and shown that AMP was anchored to the NC surface through the phosphonate group . We presumed that the role of HEPES was not only to act as the reductant but also to avoid the multichelating attachment of AMP to the NC surface.…”
Section: Figurementioning
confidence: 99%
“…The sample was thermostated for 24 h at 37 ºC. Finally, the synthesized AMP-Au NCs were purified by precipitation with acetone [31] and centrifugation (15000 rpm/30 min). After purification (removal of excess AMP), the Au NCs were redispersed in Milli-Q water.…”
Section: Preparation Of Amp-au Ncs and Amp-au Npsmentioning
confidence: 99%